WAYS OF USING THE EXPERIENCE OF FOREIGN COUNTRIES IN IMPROVING THE MECHANISMS OF PROMOTING THE EFFECTIVE USE OF INVESTMENT RESOURCES (Marketing Journal, 2025)
This article analyzes mechanisms for promoting the effective use of investment resources based on the experience of foreign countries. The investment attraction strategies of Singapore, Ireland, South Korea, China, and the United Arab Emirates are examined . Based on the analysis, practical recommendations are developed for applying advanced international practices in the context of Uzbekistan.
Keywords: investment; foreign direct investment; incentive mechanisms; special economic zones; tax benefits; investment climate